Колядування на жнивах - Творун, С. (Народна творчість та етнографія, 2007)
The article is dedicated to poorly investigated topic of harvest kolyadky (Ukrainian carols). During field expedition to Stina village of Tomashpil region in Vinnytska oblast the samples of harvest kolyadky were collected. These kolyadky were performed on the first day of harvest time. Probably, originally these songs were performed at harvest time and later they were performed at Christmas.